A Cu(I)-Based MOF with Nonlinear Optical Properties and a Favorable Optical Limit Threshold - Jing Cui; Zhaohui Yang; Yu Zhang; Zhaoxuan Fan; Jianquan Wang; Xiaoyun Qin; Lijun Gao; Haoran Yang; Shuangliang Liu; Liming Zhou; Shaoming Fang; Zhen Zhang (Nanomaterials)
The exploitation of high-performance third-order nonlinear optical (NLO) materials that have a favorable optical limit (OL) threshold is essential due to a rise in the application of ultra-intense lasers. In this study, a Cu-based MOF (denoted as Cu-bpy) was synthesized, and its third-order NLO and OL properties were investigated using the Z-scan technique with the nanosecond laser pulse excitation set at 532 nm. The Cu-bpy exhibits a typical rate of reverse saturable absorption (RSA) with a third-order nonlinear absorption coefficient of 100 cm GW−1 and a favorable OL threshold of 0.75 J cm−2 (at a concentration of 1.6 mg mL−1), which is lower than that of most NLO materials that have been reported on so far. In addition, a DFT calculation was performed and was in agreement with our experimental results. Furthermore, the mechanism of the third-order NLO properties was illustrated as one-photon absorption (1PA). These results investigate the relationship between the structure and the nonlinear optical properties of Cu-bpy, and provide an experimental and theoretical basis for its use in optical limiting applications.